A filosofia da realidade histórica de Ignacio Ellacuría como horizonte político humanizador - Baptistella, Rogerio (Universidade do Vale do Rio dos Sinos, 2012)
The present study. aims to investigate the political-humanizing proposal contained within “Filosofía de la realidad historica” (“Philosophy of the historical reality” ) (1990) by Ignacio Ellacuría. Ellacuría, in his work “Philosophy of the historical reality”, has a particular understanding of the philosophy of history, which differs from the concepts of history of modern age philosophers, nevertheless without avoiding to establish an inquiry, and presenting an exit (Ausgang) from German Idealism ; assuming a process of awareness of the transformation of historical reality. It is precisely this comprehension of differentiated history that allows us to believe, that it is possible to conduct the historical process to increasingly humanizing instances. The thesis is divided into four chapters. The first chapter addresses the issue of the constitution of the object of philosophy in Ellacuría. The objective is to analyze the dialogue that this philosopher proposes to establish with Hegel, Marx and Zubiri. It is precisely from the dialogue with these authors, that Ellacuría will present the historical reality as the object of his philosophizing. The second chapter seeks to establish the basic components that constitute the historical reality, namely: materiality, the social and personal aspects and temporality. In the third chapter, the aim is to present that there is an understanding of history in Ellacuría which differs from modernity. The historical reality considered in full, has the characteristics of praxis. It can be said therefore, that praxis is the place par excellence of the encounter between man and the world thus enabling the emergence of novum. The fourth and final chapter addresses the utopian proposal of Ellacuría. Another world is possible and necessary. The central thesis of philosophy of the historical reality of Ellacuría is precisely that the reality and the truth have to be made and discovered in the collective and successive complexity of history ,therefore history as a whole, is the perfect scenery for the apparition of another world, both possible and necessary, as a result of a utopian , politic, and ethic praxis as well as correct towards the human rights.
Keywords: História; Realidade histórica; Práxis; Sujeito; History; Historical reality; Praxis; Subject; ACCNPQ::Ciências Humanas::Filosofia